Automatic Curtain Design With LDR And IR Sensors at The BAPPENDA Kebumen - Muhammad Dzikri Maulana Syafa’at; Yulia Bherlinda (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
The Regional Revenue Management Agency of Kebumen Regency is a government agency that manages regional revenue in Kebumen Regency. The design of automatic curtains is expected to make it easier for office employees to use the facilities. This automatic curtain uses a flow chart and programming logic in designing programs for the light intensity of the IR sensor and the LDR sensor as an automatic curtain indicator using a remote. The design of the automatic curtain consists of an IR sensor and an LDR sensor as input, Arduino UNO as a processor, Relay as a component that transmits commands from the Arduino UNO to the motor, and motor as the output of this project. Automatic curtains at BAPEDA Kebumen can make it easier for employees to use office facilities to make them more durable, more comfortable, and more effective during working hours or on holidays because of the automatic curtain system that has been made.